The effects of economic and social factors toward voting behaviour of Malaysia’s young voters in 14th General Election - Tan, Jamie Yik Ki; Lau, Hooi Yee; Lee, Yee Yen; Tan, Jia Yi; Teh, Suet Yee (2019)
In this paper, we examine the effects of the variables toward the voting behaviour of Malaysia’s young voters who aged from 21 to 39. Based on this research, we study the theoretical and empirical effect brought by government debt, Goods and Services Tax (GST), inflation, unemployment, scandals, valence and social media on voting behaviour which ultimately influence the electoral outcomes. The reason of conducting this research is primarily driven by the interest to conduct further study on those relevant factors that led to the historic political change in Malaysia after the 14th General Election in 2018. In order to analyse the election’s results and understand clearly the reasons behind this outcome, it is necessary to conduct a study on the voting behaviour of Malaysia’s young voters who contributed the highest percentage of voters during the 14th General Election. Thus, the target respondents will be Malaysia’s young voters who aged from 21 to 39 whereby Universiti Tunku Abdul Rahman (UTAR) population will be the potential survey respondents. In fact, there are numerous reasons that stimulate voters to voice out via democratic system which will be discussed further in this paper. In a nutshell, this paper provides a good foundation to politicians, different parties in the financial sectors and future researchers in political marketing literature and voting behaviour research.